Effective Learning Strategies for Slow Learners Student in Indonesia: A Systematic Literature Review - Nabillah, Nadhea Aziizatun; Yoenanto, Nono Hery (Jurnal ORTOPEDAGOGIA, 2025)
Abstract: Slow learner students have several limitations in their learning process, so teachers need to have appropriate learning strategies to help and meet students' learning needs. This research aims to study appropriate and commonly used learning strategies for slow learner students in Indonesia. The research method used is systematic literature review by utilizing seven relevant articles. The results of the research show that there are several strategies that are considered effective, namely identifying student profiles and needs placing slow learner students in the front rows, reviewing material, modifying material and delivery techniques, conducting gradual teaching, small group learning, providing additional individual tutoring, using concrete learning media and technology, providing additional time, and implementing evaluation and assessment strategies for slow learner students' assignments (explaining examination procedures, reducing KKN grades, and extending daily assignment deadlines).